Economic Efficiency Rating of Russian Industrial Enterprises - Ovcharenko, Julya Vadimovna; Bessonova, Elena Anatolyevna (International Review of Management and Marketing, 2016)
The objective of this study addresses a specific rating technique to assess the efficiency of enterprise performance. The article touches upon the rating methods commonly applied to obtain a complex rating value on the basis of a comprehensive enterprise activity assessment, such as rank-sum method, rank-score method, scale interval method and rating number method. Here we present a specific approach to rating with a focus on the efficiency of enterprise performance in particular. We also give reasons for the advantages the approach we suggest obviously provides, such as time saving, gain in information content as well as applicability of the rating results as a reliable tool to a company’s productive capacity management. The article presents the results of the efficiency ratings assigned to a number of Russian industrial enterprises which are based on the assessment of their performance efficiency premised on the key efficiency values. As the result of the rating, enterprises engaged in extraction of commercial minerals have been assigned the top positions. The analysis of the indices used for calculating profitability values has led to a conclusion that profit growth and expenditure reduction will favor the raise of their efficiency and, therefore, upgrade their positions in the rating. Keywords: rating assessment, efficiency, rank-sum method, rank-score method, profitability indices, rating results. JEL Classification: L16